Reallocation of Capital and Labor within Firms - Mueller, Holger (Schweizerische Zeitschrift für Volkswirtschaft und Statistik, 2016)
Understanding how internal capital and labor markets function sheds light on one of the most fundamental questions in economics: what determines the boundaries of the firm? This essay reviews the theoretical and empirical literature on internal capital markets and firm boundaries, focusing in particular on the close link between the two subjects. Emphasis is placed on the question of how firms reallocate capital and labor internally across individual firm units in response to plausibly exogenous shocks. The essay concludes with directions for future research.